2011
DOI: 10.1007/s10735-011-9375-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of NSDHL in human peripheral tissues

Abstract: NAD(P) steroid dehydrogenase-like (NSDHL) is an X-linked gene that encodes a 3β-hydroxysteroid dehydrogenase in the cholesterol biosynthetic pathway. Loss-of-function mutations in NSDHL cause Congenital Hemidysplasia with Ichthyosiform erythroderma and Limb Defects (CHILD) and CK syndromes. CHILD syndrome is a male lethal X-linked dominant disorder characterized by asymmetric skin and limb anomalies in affected females. CK syndrome is an intellectual disability disorder characterized by disproportionate short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Topical treatment with lovastatin and cholesterol (but not cholesterol alone) virtually cleared skin lesions by 3 months, accompanied by histologic and ultrastructural normalization of epidermal structure and lipid secretion . A defective response to hedgehog signaling is also thought to play a role in disorders of cholesterol biosynthesis that share some of the skeletal and cardiovascular defects seen in CHILD syndrome. CHILD syndrome may better be categorized as a form of localized ichthyosis, because the primary defect in CHILD syndrome is one of barrier, whereas in most EN there is dysregulated growth of epidermal keratinocytes.…”
Section: Associations With Specific En Syndromesmentioning
confidence: 99%
“…Topical treatment with lovastatin and cholesterol (but not cholesterol alone) virtually cleared skin lesions by 3 months, accompanied by histologic and ultrastructural normalization of epidermal structure and lipid secretion . A defective response to hedgehog signaling is also thought to play a role in disorders of cholesterol biosynthesis that share some of the skeletal and cardiovascular defects seen in CHILD syndrome. CHILD syndrome may better be categorized as a form of localized ichthyosis, because the primary defect in CHILD syndrome is one of barrier, whereas in most EN there is dysregulated growth of epidermal keratinocytes.…”
Section: Associations With Specific En Syndromesmentioning
confidence: 99%
“…Immunohistochemical analysis of different tissues in wild‐type mouse embryos showed the highest levels of NSDHL expression in the liver, adrenal gland, testes, retina, dorsal root ganglia, and central nervous system, especially in the cortical neurons and hippocampus [Cunningham et al, ]. According to Morimoto et al, expression of the mRNA and protein encoded by human NSDHL parallels to that of mouse Nsdhl mRNA for most but not all tissues [Morimoto et al, ]. The latter study also showed that human NSDHL protein was expressed in tissues synthesizing cholesterol and steroids and in all peripheral tissues affected by CK syndrome [Morimoto et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Morimoto et al, expression of the mRNA and protein encoded by human NSDHL parallels to that of mouse Nsdhl mRNA for most but not all tissues [Morimoto et al, ]. The latter study also showed that human NSDHL protein was expressed in tissues synthesizing cholesterol and steroids and in all peripheral tissues affected by CK syndrome [Morimoto et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Na síndrome CHILD, o envolvimento ectodérmico caracteriza-se por uma eritrodermia ictiosiforme com uma demarcação na linha média do corpo, com o defeito de membro sendo ipsilateral, que pode variar desde um encurtamento de falanges e metacarpos até uma amelia de membro superior. É uma doença monogênica ligada ao X, geralmente letal no sexo masculino, decorrente de variantes de perda de função em NSDHL (Morimoto et al, 2012). O indivíduo aqui incluído (F2) era do sexo feminino, com quadro clínico compatível com esta síndrome, mas com envolvimento do membro inferior, e apresentava uma variante nonsense, não reportada previamente, em NSDHL (Mi et al, 2015).…”
Section: 33unclassified